Reduced graphene oxide loaded lamellar flower-like 3D-Co composite material
By using single-layer graphene oxide as a support in cobalt-based catalysts, the micromorphology and electron conduction capacity of Co are regulated, and the problems of catalyst agglomeration and kinetic performance are solved, and efficient and economical hydrogen production is achieved.
Patent Information
- Application Number
- CN202411025979.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2024-12-13
AI Technical Summary
The existing cobalt-based catalysts have agglomeration during the catalytic hydrolysis of sodium borohydride, resulting in rapid attenuation of cyclic performance and no obvious effect in improving the reaction kinetic performance.
Using single-layer graphene oxide as a support, graphene oxide-loaded sheet flower-like Co-3DHFLM is prepared by hydrothermal method, and then high-temperature hydrogen reduction method is used to prepare the reduced graphene oxide-loaded sheet flower-like 3D-Co composite material to improve the catalyst Specific surface area and electron conduction ability reduce activation energy.
The catalytic efficiency was significantly improved, the maximum hydrogen production rate reached 4000.00-4500.00 mL/min·g, the activation energy was reduced to 26.4-29.8 kJ/mol, the cycling performance retained the initial activity by 77.24%, and the cost of the catalyst was reduced.
Smart Images

Figure CN119114079A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyzing the hydrolysis of sodium borohydride to produce hydrogen, and in particular to a reduced graphene oxide-loaded lamellar flower-shaped 3D-Co composite material. Background Art
[0002] Among hydrogen energy materials, the hydrogen storage capacity of NaBH4 reaches 10.8wt%, but the self-hydrolysis process under normal temperature is slow, so a catalyst is used to increase the hydrogen production rate. At present, among the common non-precious metal catalysts, Co-based catalysts have the characteristics of excellent comprehensive performance and relatively low cost. For example, the existing document 1 (T. Pfeil, T. Pourpoint, L. Groven. Effects of crystallinity and morphology of solution combustion synthesized Co3O4 as a catalyst precursor in hydrolysis of sodium borohydride [J]. International Journal of Hydrogen Energy, 2014, 39 (5): 2149-2159.) uses Co3O4 powder as a catalyst for sodium borohydride hydrolysis to produce hydrogen, and its maximum hydrogen production rate is 1240mL / min·g, and the activation energy is 54.1kJ / mol. Although this technical solution successfully achieves the improvement of the hydrogen production rate of sodium borohydride hydrolysis, due to the agglomeration of Co3O4 powder during the catalytic process, the cycle performance is rapidly attenuated.
[0003] In order to solve the above-mentioned problem of agglomeration of active particles, carbon materials can be introduced as carriers to improve the dispersibility of active particles, thereby improving the catalytic activity of the catalyst and reducing material costs. For example, existing document 2 (Jing Jiang, Shiyu Yang, Huili Lei, et al. Highly dispersed cobalt nanoparticles onto nitrogen-doped carbon nanosheets for efficient hydrogen generation via catalytic hydrolysis of sodium borohydride [J]. International Journal of Hydrogen Energy, 2021, 46: 32403-32412.) By using 2-methylimidazole and melamine as reaction sources, nitrogen-doped carbon is introduced as a carrier to achieve uniform and dense dispersion of Co nanoparticles, and the resulting Co@NC has high activity for the catalytic hydrolysis of NaBH4, with a maximum hydrogen production rate of 2574 mL / min·g and an activation energy of 47.6 kJ / mol. This technical solution improves the catalytic activity and cycle performance by introducing nitrogen-doped carbon materials as carriers, but has no obvious effect on the reaction activation energy, that is, the improvement of reaction kinetics.
[0004] The basic principle of improving reaction kinetics and reducing activation energy is to improve the electron transfer efficiency and increase the specific surface area by improving the electronic conductivity and stability of the composite material, thereby obtaining the technical effect of improving catalytic efficiency and stability and reducing reaction activation energy. For example, existing document 3 (Xianli Wu, Xiaoyu Zhang, Guosheng Han, et al. Reaction of Co3O4 nanocrystals on graphene sheets to fabricate excellent catalysts for hydrogen generation [J]. ACS Sustain Chem Eng. 2018, 6 (7): 8427-8436.) uses Co3O4 nanoparticles to modify and adjust graphene sheets, changing the effective electron transfer in the catalytic process, and achieving a maximum hydrogen production rate of 2696 mL / min·g and an activation energy of 28.3 kJ / mol. Therefore, CoO x -GCNFs have a significant effect on increasing the maximum hydrogen production rate and reducing the reaction activation energy for NaBH4 hydrolysis.
[0005] In summary, the introduction of carriers into cobalt-based catalysts can improve the hydrogen production rate and activation energy of NaBH4 hydrolysis. In particular, when graphene is used as a carrier, due to its unique two-dimensional structure and high electronic conductivity, it can effectively promote electron transport, reduce the activation energy of the reaction, and thus accelerate the hydrolysis process; in addition, the morphology of the catalyst can be regulated by controlling the synthesis conditions, which also has a significant effect on the performance of the cobalt-based catalyst.
[0006] Therefore, by loading graphene carriers and adjusting the morphology of cobalt-based catalysts, more efficient catalysts can be prepared, which can significantly increase the hydrogen production rate of NaBH4 hydrolysis, reduce the reaction activation energy, and ultimately achieve more economical and efficient hydrogen production. Summary of the invention
[0007] The invention aims to provide a reduced graphene oxide-loaded lamellar flower-shaped 3D-Co composite material.
[0008] The present invention aims at solving the technical problems existing in the prior art by adopting the following principles and methods:
[0009] 1. Using single-layer graphene oxide as a carrier, the microscopic morphology of Co3O4 can be regulated to increase the specific surface area of the catalyst. Then, 3D-Co can be obtained by using Co metal as an active substance to improve the catalytic efficiency.
[0010] 2. Reduced graphene oxide is used as a carrier. The high electron conductivity and stability of reduced graphene oxide are utilized to further improve electron transmission and increase specific surface area when compounded with 3D-Co, which significantly improves catalytic efficiency and greatly reduces activation energy.
[0011] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:
[0012] A reduced graphene oxide loaded lamellar flower-shaped 3D-Co composite material, firstly, preparing a graphene oxide loaded lamellar flower-shaped Co-3DHFLM composite material by a hydrothermal method, and then preparing a reduced graphene oxide loaded lamellar flower-shaped 3D-Co composite material by a high-temperature hydrogen reduction method;
[0013] The raw materials for preparing the Co-3DHFLM / GO are cobalt nitrate hexahydrate, 2-methylimidazole, monolayer graphene oxide, and methanol;
[0014] The reducing gas for preparing the 3D-Co / rGO is a hydrogen-argon mixed gas;
[0015] The overall 3D-Co / rGO is a nanoflower morphology loaded on a nanosheet, specifically composed of 3D-Co and rGO. The microstructure of rGO is a single-layer sheet structure, and the microstructure of 3D-Co is a lamellar flower structure with a size of 2-4 μm. 3D-Co is loaded on the surface of rGO.
[0016] The 3D-Co / rGO has magnetic properties.
[0017] A method for preparing a reduced graphene oxide-supported lamellar flower-shaped 3D-Co composite material comprises the following steps:
[0018] Step 1, preparation of lamellar flower-like Co-3DHFLM / GO, first, adding a single layer of graphene oxide GO to methanol for ultrasonication to obtain a GO solution of a certain concentration, then adding cobalt nitrate hexahydrate to the GO solution and stirring to obtain solution A, at the same time, dissolving 2-methylimidazole in methanol and stirring to obtain solution B, then slowly dropping solution B into solution A, stirring evenly to obtain a reaction solution; finally, under certain conditions, subjecting the reaction solution to a hydrothermal reaction, after the reaction is complete, washing and drying the reaction product to obtain a graphene oxide-loaded lamellar flower-like Co-3DHFLM / GO composite material, i.e., lamellar flower-like Co-3DHFLM / GO, referred to as Co-3DHFLM / GO;
[0019] In step 1, the concentration of the GO solution is 0.6 mg / mL; the mass ratio of GO, cobalt nitrate hexahydrate and 2-methylimidazole is 15:873:328;
[0020] In step 1, the conditions for the hydrothermal reaction are: the reaction temperature is 120° C. and the reaction time is 1.5 h;
[0021] Step 2, preparation of lamellar flower-like 3D-Co / rGO, under certain conditions, the Co-3DHFLM / GO obtained in step 1 is subjected to high-temperature reduction to obtain a reduced graphene oxide-supported lamellar flower-like 3D-Co composite material, i.e., lamellar flower-like 3D-Co / rGO, referred to as 3D-Co / rGO;
[0022] In step 2, the high-temperature reduction conditions are: the reducing gas is hydrogen, the reduction temperature is 500° C., and the reduction time is 3 hours.
[0023] A reduced graphene oxide loaded lamellar flower-shaped 3D-Co composite material, when used as a catalyst for hydrogen production by hydrolysis of sodium borohydride, has a maximum hydrogen production rate of 4000.00-4500.00 mL / min·g at 303K, and the amount of hydrogen released reaches 100% of the theoretical value. The activation energy of catalytic hydrogen release is E a=26.4-29.8 kJ / mol; at 303 K, after 5 times of recycling / reuse, it retains 77.24% of the initial catalytic activity.
[0024] The technical effect of the present invention can be known by the following tests:
[0025] XRD test shows that the diffraction peak of 3D-Co / rGO is mainly cobalt metal, and there is also a small amount of characteristic peak of cobalt oxide. The reason is that the characteristic peak of cobalt oxide is due to the inevitable oxidation during the test. The test results show that the cobalt element in 3D-Co / rGO exists in the form of cobalt metal, that is, through the high-temperature reduction of step 2, Co-3DHFLM is reduced to 3D-Co; at the same time, graphene oxide is reduced to reduced graphene oxide at high temperature.
[0026] SEM detection shows that the overall morphology of 3D-Co / rGO is a coral-like nanoflower loaded on nanosheets, which is specifically composed of two parts: 3D-Co and rGO. Among them, the micromorphology of rGO is a single-layer lamellar structure, and the micromorphology of 3D-Co is a coral-like structure with a size of 2-4μm. 3D-Co is loaded on the surface of rGO.
[0027] EDS detection shows that 3D-Co / rGO contains C, O, N and Co elements at the same time, and each element is evenly distributed.
[0028] Magnetic testing shows that 3D-Co / rGO is a magnetic material, which is conducive to recycling and improves the cycle performance.
[0029] A reduced graphene oxide-loaded lamellar flower-shaped 3D-Co composite material is characterized in that when used as a catalyst for producing hydrogen by hydrolyzing sodium borohydride, the maximum hydrogen production rate of sodium borohydride at 303K is 4000.00-4500.00 mL / min·g, and the amount of hydrogen released reaches 100% of the theoretical value.
[0030] The activation energy of catalytic hydrogen release is Ea = 26.4-29.8 kJ / mol.
[0031] At 303 K, 77.24% of the initial catalytic activity was retained after 5 recycling / reuses.
[0032] Therefore, the present invention has the following advantages:
[0033] 1. Using GO as a carrier, the microstructure of the cobalt source is regulated to obtain Co-3DHFLM, which is then reduced to obtain 3D-Co, so that Co metal is used as an active substance, which greatly reduces Ea;
[0034] 2. Using rGO carrier to load coral-like 3D-Co. rGO has excellent electron conductivity and stability. Doping with 3D-Co is beneficial to electron transmission and increasing specific surface area, which can significantly improve catalytic efficiency and greatly reduce activation energy.
[0035] 3. 3D-Co is a coral-like structure with a highly interconnected three-dimensional network structure, which increases the specific surface area of the catalyst, thereby increasing the exposure of active sites and helping to improve catalytic efficiency;
[0036] 4. Direct activation after hydrothermal treatment, simple synthesis process and short reaction cycle;
[0037] 5. Using non-precious metal Co instead of precious metal as catalyst increases the hydrogen production rate while reducing the catalytic cost;
[0038] 6. It has magnetism. Magnetic recovery replaces the traditional suction filtration recovery method, which can effectively improve the problems of oxidation and shedding during its use, greatly reduce the process difficulty of the recovery process and the damage to the microscopic morphology of the material, and improve the stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 XRD patterns of 3D-Co, 3D-Co / GO and 3D-Co / rGO composite materials in Example 1;
[0040] Figure 2 is the SEM image of 3D-Co / GO in Example 1;
[0041] Figure 3 This is a comparison chart of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, and Comparative Example 5 catalyzing the hydrolysis and hydrogenation of sodium borohydride at a temperature of 303K.
[0042] Figure 4 is the EDS graph of the corresponding elements of 3D-Co / rGO in Example 1;
[0043] Figure 5 is the SEM image of 3D-Co / rGO in Example 1;
[0044] Figure 6 This is a diagram of hydrogen production by catalyzing sodium borohydride hydrolysis at different temperatures by 3D-Co / rGO in Example 1;
[0045] Figure 7 is the activation energy diagram of 3D-Co / rGO in Example 1;
[0046] Figure 8 This is an experimental diagram showing the magnetic properties of 3D-Co / rGO in Example 1;
[0047] Fig. 9 This is a cycle performance diagram of 3D-Co / rGO in Example 1 catalyzing sodium borohydride hydrolysis and hydrogenation for 6 cycles at 303K;
[0048] Fig.10 is the SEM image of Co-3DHFLM in Comparative Example 1;
[0049] Fig.11 This is the SEM image of 3D-Co in Comparative Example 1. DETAILED DESCRIPTION
[0050] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0051] Example 1
[0052] A method for preparing a reduced graphene oxide-loaded lamellar flower-shaped 3D-Co composite material, the specific steps are as follows:
[0053] Step 1, preparation of lamellar flower-like Co-3DHFLM / GO, first, add 15 mg of single-layer graphene oxide GO to 25 mL of methanol for ultrasonication to obtain a GO solution with a concentration of 0.6 mg / mL, then add 0.873 g of cobalt nitrate hexahydrate to the GO solution and stir to obtain solution A, and at the same time, dissolve 0.328 g of 2-methylimidazole in methanol and stir to obtain solution B, then slowly add solution B dropwise to solution A, stir evenly to obtain a reaction solution; finally, at a reaction temperature of 120° C. and a reaction time of 1.5 h, the reaction solution is subjected to a hydrothermal reaction, and after the reaction is completed, the reaction product is washed and dried to obtain a graphene oxide-loaded lamellar flower-like Co-3DHFLM / GO composite material, that is, lamellar flower-like Co-3DHFLM / GO, referred to as Co-3DHFLM / GO;
[0054] In order to prove the crystal structure of Co-3DHFLM / GO, XRD test was performed. The test results are shown in Figure 1 As shown, the diffraction peak of Co-3DHFLM / GO is consistent with that of Co-3DHFLM in the reference. In addition, the diffraction peak of Co-3DHFLM / GO shifts to the left. The reason is that the added GO increases the lattice spacing of Co-3DHFLM.
[0055] In order to verify the microstructure of Co-3DHFLM / GO, SEM test was performed. The test results are shown in Figure 2 As shown, Co-3DHFLM is a lamellar flower-like structure with a size of 3-5 μm and is loaded on flake GO.
[0056] In order to compare the hydrogen production performance by hydrolysis with that of 3D-Co / rGO obtained in the subsequent step 2, the Co-3DHFLM / GO obtained in step 1 was tested for hydrogen production by hydrolysis.
[0057] The specific method of the hydrolysis hydrogen production test is: carry out the hydrogen production test under the temperature conditions set in the experiment, put a solution containing 1.5wt.% NaBH4 and 5wt.% NaOH into a constant temperature water bath, and after reaching equilibrium at the aforementioned set temperature; take out 10mL and add it to a wide-mouth bottle containing a catalyst, collect and record the volume of hydrogen produced per unit time by the drainage method, and the hydrogen release rate can be obtained. Among them, the temperature condition is 303K unless otherwise specified.
[0058] The test results of the hydrolysis hydrogen production performance of Co-3DHFLM / GO are as follows Figure 3 As shown, at 303K, the hydrogen production rate of sodium borohydride is 400.89mL / min·g.
[0059] Step 2, preparation of lamellar flower-like 3D-Co / rGO, under the conditions of hydrogen as reducing gas, reduction temperature of 500°C, and reduction time of 3h, the Co-3DHFLM / GO obtained in step 1 is subjected to high-temperature reduction to obtain a reduced graphene oxide-loaded lamellar flower-like 3D-Co composite material, i.e., lamellar flower-like 3D-Co / rGO, referred to as 3D-Co / rGO.
[0060] In order to prove the crystal structure of 3D-Co / rGO, XRD test was carried out. The test results are shown in Figure 1 As shown, the diffraction peak of 3D-Co / rGO is mainly cobalt metal, and there is also a small amount of characteristic peaks of cobalt oxide. The reason is that the characteristic peaks of cobalt oxide are caused by the inevitable oxidation during the test. The test results show that the cobalt element in 3D-Co / rGO exists in the form of cobalt metal, that is, through the high-temperature reduction of step 2, Co-3DHFLM is reduced to 3D-Co; at the same time, graphene oxide is reduced to reduced graphene oxide at high temperature.
[0061] In order to verify the element composition and element distribution of 3D-Co / rGO, EDS test was performed. The test results are shown in Figure 4 As shown, 3D-Co / rGO contains C, O, N and Co elements at the same time, and each element is evenly distributed.
[0062] In order to verify the microstructure of 3D-Co / rGO, SEM test was performed. The test results are shown in Figure 5As shown, the 3D-Co / rGO as a whole is a coral-like nanoflower morphology loaded on a nanosheet, specifically composed of 3D-Co and rGO, wherein the microscopic morphology of rGO is a single-layer lamellar structure, the microscopic morphology of 3D-Co is a coral-like structure, the size is 2-4μm, and 3D-Co is loaded on the surface of rGO. A longitudinal comparison with the Co-3DHFLM / GO obtained in step 1 shows that the high-temperature reduction in step 2 converts the lamellar flower-like Co-3DHFLM into coral-like 3D-Co, that is, the microstructure is adjusted. The test results show that the lamellar flower-like 3D-Co is transformed into a coral-like structure after high-temperature reduction, and the cobalt element is reduced, which can theoretically improve the transmission efficiency of the material and improve the catalytic activity.
[0063] In order to prove the hydrogen production performance of 3D-Co / rGO as a catalyst for hydrogen production from sodium borohydride hydrolysis, a hydrolysis hydrogen production test was carried out. The test results are shown in Table 1 and Figure 3 As shown in the figure, under 303K, the maximum hydrogen production rate of sodium borohydride is 4251.10mL / min·g, and the hydrogen release amount reaches 100% of the theoretical value. Compared with the Co-3DHFLM / GO obtained in step 1, the maximum hydrogen production rate of 3D-Co / rGO is increased by 960.4%.
[0064] In order to prove the reaction kinetics of 3D-Co / rGO, water splitting and hydrogen production tests were carried out at 298K, 303K, 308K, and 313K. The test results are shown in Figure 2. Figure 6 As shown in Table 1 and Figure 7 As shown, the apparent activation energy of the reaction is Ea=28.1 kJ / mol; at the same time, in order to compare with the prior art, the data of the references are summarized in Table 1.
[0065] Table 1 Hydrogen production rate and activation energy of NaBH4 hydrolysis catalyzed by different catalysts
[0066]
[0067] Note: The reference numbers in Table 1 correspond to the following documents:
[0068] [1]T.Pfeil,T.Pourpoint,L.Groven.Effects of crystallinity andmorphology of solution combustion synthesized Co3O4 as a catalyst precursor inhydrolysis of sodium borohydride[J].International Journal of Hydrogen Energy,2014,39(5):2149-2159.
[0069] [2]Xianli Wu,Xiaoyu Zhang,Guosheng Han,et al.Reaction of Co3O4nanocrystals on graphene sheets to fabricate excellent catalysts for hydrogengeneration[J].ACS Sustain Chem Eng.2018,6(7):8427-8436.
[0070] [3]Jing Jiang,Shiyu Yang,Huili Lei,et al.Highly dispersed cobaltnanoparticles onto nitrogen-doped carbon nanosheets for efficient hydrogengeneration via catalytic hydrolysis of sodium borohydride[J].InternationalJournal of Hydrogen Energy,2021,46(64):32403-32412.
[0071] [4]S.Gupta,N.Patel,R.Fernandes,et al.Mesoporous Co-B nanocatalyst forefficient hydrogen production by hydrolysis of sodium borohydride[J].International Journal of Hydrogen Energy,2013,38(34):14685-14692.
[0072] Through the above test results and comparative analysis with existing references, the following conclusions can be drawn preliminarily:
[0073] 1. By comparing reference [1] and reference [2], it can be seen that both of them are based on cobalt oxide as the active material. The Co3O4 powder in reference [1] has poor HGR and Ea because no carrier is used. However, reference [2] introduces GCNFs as a carrier, which significantly improves the HGR to 217.4% of that in reference [1]. At the same time, combined with Ea, it can be seen that the introduction of a carrier can significantly reduce Ea to 52.3% of that in reference [1]. That is, the introduction of a carrier can improve the reaction kinetics and thus improve the catalytic performance. The principle is that GCNFs can improve the electron transfer in the catalytic process.
[0074] 2. By comparing reference [2] and reference [3], it can be seen that reference [2] also uses carbon materials as carriers and uses Co metal as active material. Compared with reference [2], although HGR only slightly decreases, Ea is greatly increased to 47.6. This phenomenon shows that using Co metal as active material will reduce the reaction kinetics, while the lack of significant decrease in HGR indicates that the reaction thermodynamics is improved.
[0075] 3. Further comparison of references [2] and [3] with reference [3] shows that replacing P123 with NC as the carrier results in a slight increase in HGR and no essential change in the basic rule that the activation energy cannot be effectively reduced. That is, those skilled in the art can draw the following conclusions from references [2], [3] and [4]: based on Co metal as the active substance, the introduction of the carrier can only improve the thermodynamic performance of the reaction, but cannot effectively reduce the activation energy and improve the reaction kinetics.
[0076] 4. Based on the above conclusions, the present invention uses GO as a carrier to achieve the regulation of the microstructure of the cobalt source, obtain Co-3DHFLM, and then after reduction, use Co metal as an active substance to significantly reduce Ea, reaching the level of Ea obtained in reference [2], and slightly exceeding it. At the same time, a significant improvement in HGR is achieved. That is, when the present invention uses cobalt oxide as an active substance, the introduction of a carrier significantly reduces the activation energy Ea, improves the reaction kinetics, and uses Co metal as an active substance to significantly improve the reaction thermodynamics.
[0077] Based on the above analysis, the reasons why the catalytic performance of the present invention is significantly improved compared with the prior art can be simply summarized as follows:
[0078] 1. GO is used as a carrier to achieve the technical effect of regulating the microscopic morphology of the cobalt source and increasing the specific surface area of the catalyst. Then 3D-Co is obtained through the original method, and Co metal is used as an active substance to improve the catalytic efficiency.
[0079] 2. Using rGO as a carrier, taking advantage of the high electron conductivity and stability of rGO, when combined with 3D-Co, further improves electron transmission and increases specific surface area, significantly improves catalytic efficiency, and greatly reduces activation energy.
[0080] According to the previous research results of the inventor's research group, the catalyst can be efficiently separated from the reaction liquid by magnetic recovery of the catalyst. In order to prove that the 3D-Co / rGO composite material has magnetic properties, a magnetic test was conducted. The magnetic test results are as follows: Figure 8 As shown, 3D-Co / rGO is attached to the surface of the magnetic stirring bar. The test results show that 3D-Co / rGO has magnetic properties, that is, the catalyst can be recovered by magnetic force.
[0081] In order to prove the cycle performance of 3D-Co / rGO, a cycle performance test was conducted. The specific method of the cycle performance test is: after the 3D-Co / rGO that has been subjected to the hydrogen release test is recovered by magnetic force, the aforementioned hydrolysis hydrogen production test is performed again to obtain the hydrogen release rate after the cycle, and the cycle performance of 3D-Co / rGO can be obtained by simple calculation. The test results are shown in Table 2 and Fig. 9 As shown, under 303K conditions, after 5 cycles, 77.24% of the initial catalytic activity was still retained; after 6 cycles, 72.9% of the initial catalytic activity was still retained; at the same time, in order to compare with the prior art, the data of the references are summarized in Table 2.
[0082] Table 2 Cycle number and cycle performance of NaBH4 hydrolysis catalyzed by different catalysts
[0083] catalyst Cycle times Cycle performance Reference number Co / MWCNTs-20 5 34.28% [5] Co@3DGO 5 70.00% [6] 3D-Co / rGO 5 77.24% The present invention
[0084] Note: The reference numbers in Table 2 correspond to the following documents:
[0085] [5]Katabathini Narasimharao,Bahaa M.Abu-Zied,Sulaiman YahyaAlfaifi.Cobalt oxide supported multi wall carbon nanotube catalysts for hydrogen production via sodium borohydride hydrolysis[J].InternationalJournal of Hydrogen Energy,2021,46(9):6404-6418.
[0086] [6]Lan Yang,Nan Cao,Cheng Du,et al.Graphene supported cobalt(0)nanoparticles for hydrolysis of ammonia borane[J].Materials Letters, 2014,115:113-116.
[0087] Through the above test results and comparative analysis with existing references, the following conclusions can be drawn preliminarily:
[0088] Based on the use of Co metal as the active substance, different carbon materials as carriers have significant differences in cycle performance;
[0089] Specifically, by comparing reference [6] with the present invention, it can be seen that reference [6] maintains graphene in an oxidized state, i.e., graphene oxide GO, while the present invention reduces GO to rGO while reducing Co-3DHFLM to 3D-Co, thereby achieving further improvement in cycle performance without increasing production steps.
[0090] Based on the above analysis, the reasons why the cycle performance of the present invention is significantly improved compared with the prior art can be simply summarized as follows:
[0091] 1. Use two-dimensional reduced graphene oxide as a carrier to improve the stability of the overall microstructure of the catalyst during the reaction, that is, it is not easy to collapse, thereby effectively enhancing the stability of the catalyst;
[0092] 2. After high-temperature hydrogen reduction, 3D-Co / rGO uses the carbon contained in 3D-Co itself as the carbon skeleton to achieve the technical effect of anchoring the cobalt source, so that the catalyst remains stable during the cycle, that is, it is not easy to agglomerate.
[0093] In order to demonstrate the role of GO in the technical solution, Comparative Example 1 is provided, in which a 3D-Co material is prepared without adding GO.
[0094] Comparative Example 1
[0095] A method for preparing a 3D-Co material without adding GO, wherein the steps not specifically described are the same as those in Example 1, except that: in step 1, GO is not added, wherein the material obtained in step 1 is Co-3DHFLM prepared without adding GO, referred to as Co-3DHFLM for short; the material obtained in step 2 is a 3D-Co material prepared without adding GO, referred to as 3D-Co for short.
[0096] The SEM test results of Co-3DHFLM obtained in step 1 are as follows: Fig.10 As shown, the Co-3DHFLM nanoparticles present a flower-like structure composed of two-dimensional nanosheets, and at the same time, there is agglomeration phenomenon;
[0097] The SEM test results of 3D-Co obtained in step 2 are as follows: Fig.11 As shown, the 3D-Co nanoparticles present a coral-like structure and there is agglomeration phenomenon.
[0098] A longitudinal comparison of the Co-3DHFLM obtained in step 1 and the 3D-Co obtained in step 2 shows that high-temperature reduction can also adjust the micromorphology of the material, which is consistent with the high-temperature reduction effect in Example 1; however, high-temperature reduction cannot solve the agglomeration problem.
[0099] A lateral comparison of the Co-3DHFLM obtained in step 1 and the Co-3DHFLM / GO obtained in step 1 of Example 1 shows that the addition of GO can effectively improve the dispersibility of Co-3DHFLM and solve the agglomeration problem.
[0100] A lateral comparison between the 3D-Co obtained in step 2 and the 3D-Co / rGO obtained in step 2 of Example 1 also proves that the addition of GO can effectively improve the dispersibility of 3D-Co and solve the agglomeration problem.
[0101] The test results of hydrolysis hydrogen production of Co-3DHFLM obtained in step 1 are as follows Figure 3 As shown, under 303K conditions, the maximum hydrogen production rate is 1283.60mL / min·g, and the hydrogen release amount reaches 100% of the theoretical value;
[0102] The test results of hydrolysis and hydrogen production of 3D-Co obtained in step 2 are as follows Figure 3 As shown, under 303K conditions, the maximum hydrogen production rate is 1708.15mL / min·g, and the hydrogen release amount reaches 100% of the theoretical value.
[0103] A longitudinal comparison of the Co-3DHFLM obtained in step 1 and the 3D-Co obtained in step 2 shows that high-temperature reduction can increase the maximum hydrogen production rate by 33%, which is consistent with the high-temperature reduction effect in Example 1.
[0104] A lateral comparison of the Co-3DHFLM obtained in step 1 and the Co-3DHFLM / GO obtained in step 1 of Example 1 shows that the addition of GO reduces the maximum hydrogen production rate from 1283.60 mL / min·g to 400.89 mL / min·g. The reason is that since GO only acts as a carrier, after adding GO, the content of Co-3DHFLM decreases, which directly leads to a decrease in the active sites with catalytic effect, thereby reducing the catalytic activity.
[0105] By comparing the 3D-Co obtained in step 2 with the 3D-Co / rGO obtained in step 2 of Example 1, it can be seen that the addition of GO increases the maximum hydrogen production rate from 1708.15 mL / min·g to 4251.10 mL / min·g, an increase of 148.87%. Combined with the conclusion of step 1, it can be seen that although the addition of GO leads to a decrease in the content of Co-3DHFLM, after high-temperature reduction, the maximum hydrogen production rate of 3D-Co / rGO is significantly increased. The reason is that the conductivity of the rGO obtained after high-temperature reduction is enhanced, which significantly reduces the activation energy of hydrolysis to produce hydrogen, thereby improving the catalytic activity.
[0106] Combining the above SEM test results and hydrolysis hydrogen production test results, it can be proved that the role of GO in the technical solution is that GO, as a carrier, effectively enhances the dispersion of the catalyst, thereby effectively inhibiting the agglomeration of 3D-Co nanoparticles during the reaction process, and ultimately significantly improves the maximum hydrogen release rate of sodium borohydride.
[0107] In order to demonstrate the effect of the amount of graphene oxide added on the catalytic performance, Comparative Examples 2 and 3 are provided, in which the composite materials are prepared with the addition amounts of GO being 10 mg and 20 mg, respectively.
[0108] Comparative Example 2
[0109] A 3D-Co / rGO composite material with 10 mg of GO added was prepared. The steps not specifically described were the same as those in Example 1, except that in step 1, 10 mg of GO was added. The obtained material was referred to as 3D-Co / rGO-10.
[0110] The test results of 3D-Co / rGO-10 for hydrogen production by hydrolysis, such as Figure 3As shown, under 303K conditions, the maximum hydrogen production rate of sodium borohydride is 3340.00 mL / min·g, and the amount of hydrogen released reaches 100% of the theoretical value. By comparison with Example 1, it can be seen that the hydrogen production performance of sodium borohydride in Example 1 is improved by 27.3% compared with Comparative Example 2. The reason is that the small amount of GO added leads to supersaturation when loading 3D-Co nanoparticles, which is specifically manifested in the obvious agglomeration of the composite material, thereby reducing the hydrogen production rate of the sodium borohydride hydrolysis reaction.
[0111] Comparative Example 3
[0112] A 3D-Co / rGO composite material with 20 mg of GO added was prepared. The steps not specifically described were the same as those in Example 1, except that 20 mg of graphene oxide was added in step 1, and the obtained material was recorded as 3D-Co / rGO-20.
[0113] The test results of 3D-Co / rGO-20 for hydrogen production by hydrolysis are shown in Figure 3 As shown in the figure, under 303K, the maximum hydrogen production rate of sodium borohydride is 3008.18mL / min·g, and the amount of hydrogen released reaches 100% of the theoretical value. By comparison with Example 1, it can be seen that the hydrogen production performance of Example 1 is improved by 41.3% compared with Comparative Example 5. The reason is that excessive addition of GO leads to a decrease in the relative loading of 3DCo nanoparticles, resulting in a decrease in active sites, thereby reducing the hydrogen production rate of the sodium borohydride hydrolysis reaction.
[0114] It can be seen from Example 1 and Comparative Examples 2 and 3 that the amount of GO added has a significant effect on the catalytic performance.
Claims
1. A reduced graphene oxide-loaded lamellar flower-shaped 3D-Co composite material, characterized in that: Firstly, a graphene oxide-supported lamellar flower-shaped Co-3DHFLM composite material was prepared by a hydrothermal method, and then a reduced graphene oxide-supported lamellar flower-shaped 3D-Co composite material was prepared by a high-temperature hydrogen reduction method; The raw materials for preparing the Co-3DHFLM / GO are cobalt nitrate hexahydrate, 2-methylimidazole, monolayer graphene oxide, and methanol; The reducing gas for preparing the 3D-Co / rGO is a hydrogen-argon mixed gas.
2. The 3D-Co composite material according to claim 1, characterized in that: The overall morphology of 3D-Co / rGO is nanoflowers loaded on nanosheets, and is specifically composed of two parts: 3D-Co and rGO. The micromorphology of rGO is a single-layer lamellar structure, and the micromorphology of 3D-Co is a lamellar flower structure with a size of 2-4μm. 3D-Co is loaded on the surface of rGO.
3. The 3D-Co composite material according to claim 1, characterized in that: The 3D-Co / rGO has magnetic properties.
4. A method for preparing a reduced graphene oxide loaded lamellar flower-shaped 3D-Co composite material, characterized in that The following steps are involved: Step 1, preparation of lamellar flower-like Co-3DHFLM / GO, first, adding a single layer of graphene oxide GO to methanol for ultrasonication to obtain a GO solution of a certain concentration, then adding cobalt nitrate hexahydrate to the GO solution and stirring to obtain solution A, at the same time, dissolving 2-methylimidazole in methanol and stirring to obtain solution B, then slowly dropping solution B into solution A, stirring evenly to obtain a reaction solution; finally, under certain conditions, subjecting the reaction solution to a hydrothermal reaction, after the reaction is complete, washing and drying the reaction product to obtain a graphene oxide-loaded lamellar flower-like Co-3DHFLM / GO composite material, i.e., lamellar flower-like Co-3DHFLM / GO, referred to as Co-3DHFLM / GO; Step 2, preparation of lamellar flower-like 3D-Co / rGO, under certain conditions, the Co-3DHFLM / GO obtained in step 1 is subjected to high-temperature reduction to obtain a reduced graphene oxide-loaded lamellar flower-like 3D-Co composite material, i.e., lamellar flower-like 3D-Co / rGO, referred to as 3D-Co / rGO.
5. The preparation method according to claim 4, characterized in that: In step 1, the concentration of the GO solution is 0.6 mg / mL; the mass ratio of GO, cobalt nitrate hexahydrate and 2-methylimidazole is 15:873:328; In step 1, the conditions for the hydrothermal reaction are: reaction temperature is 120° C., and reaction time is 1.5 h.
6. The preparation method according to claim 4, characterized in that: In step 2, the high-temperature reduction conditions are: the reducing gas is hydrogen, the reduction temperature is 500° C., and the reduction time is 3 hours.
7. A reduced graphene oxide loaded lamellar flower-shaped 3D-Co composite material, characterized in that: When used as a catalyst for producing hydrogen by hydrolysis of sodium borohydride, the maximum hydrogen production rate of sodium borohydride at 303K is 4000.00-4500.00 mL / min·g, and the amount of hydrogen released reaches 100% of the theoretical value.
8. A reduced graphene oxide loaded lamellar flower-shaped 3D-Co composite material, characterized in that: When used as a catalyst for hydrogen production by hydrolysis of sodium borohydride, the activation energy of catalytic hydrogen release is E a =26.4-29.8 kJ / mol.
9. A reduced graphene oxide-loaded lamellar flower-shaped 3D-Co composite material, characterized in that: When used as a catalyst for hydrogen production by hydrolysis of sodium borohydride, at 303K, after 5 times of recycling / reuse, it retains 77.24% of the initial catalytic activity.
